b - Hu, Xiaolin; Xia, Yousheng; Zhang, Yunong; Zhao, Dongbin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The volume LNCS 9377 constitutes the refereed proceedings of the 12th International Symposium on Neural Networks, ISNN 2015, held in Jeju, South Korea in October 2015. The 55 revised full papers presented were carefully reviewed and selected from 97 submissions. These papers cover many topics of neural network-related research including intelligent control, neurodynamic analysis, memristive neurodynamics, computer vision, signal processing, machine learning, and optimization.
Intelligent Control -- A Novel T-S Fuzzy Model Based Adaptive Synchronization Control Scheme for Nonlinear Large-Scale Systems with Uncertainties and Time-Delay -- Finite-Time Control for Markov Jump Systems with Partly Known Transition Probabilities and Time-Varying Polytopic Uncertainties -- Hybrid Function Projective Synchronization of Unknown Cohen-Grossberg Neural Networks with Time Delays and Noise Perturbation -- Neural Dynamic Surface Control for Three-Phase PWM Voltage Source Rectifier -- A Terminal-Sliding-Mode-Based Frequency Regulation -- A New Discrete-Time Iterative Adaptive Dynamic Programming Algorithm Based on Q-Learning -- Adaptive Neural Network Control for a Class of Stochastic Nonlinear Strict-Feedback Systems -- Event-Triggered H1 Control for Continuous-Time Nonlinear System -- Adaptive Control of a Class of Nonlinear Systems with Parameterized Unknown Dynamics -- H-infinity Control Synthesis for Linear Parabolic PDE Systems with Model-Free Policy Iteration -- Exponential Synchronization of Complex Delayed Dynamical Networks with Uncertain Parameters via Intermittent Control -- Inverse-Free Scheme of G1 Type to Velocity-Level Inverse Kinematics of Redundant Robot Manipulators -- Design of Fuzzy-Neural-Network-Inherited Backstepping Control for Unmanned Underwater Vehicle -- Neurodynamics Analysis -- A New Sampled-Data State Estimator for Neural Networks of Neutral-Type with Time-Varying Delays -- Exponential Lag Synchronization for Delayed Cohen-Grossberg Neural Networks with Discontinuous Activations -- Mean Square Exponential Stability of Stochastic Delayed Static Neural Networks With Markovian Switching -- Robust Multistability and Multiperiodicity of Neural Networks with Time Delays -- A Novel Four-Dimensional Memristive Hyperchaotic System with Its Analog Circuit Implementation -- Memristor Crossbar Array for Image Storing -- Lagrange Stability for Memristor-Based Neural Networks with Time-Varying Delay via Matrix Measure -- Multistability of Memristive Neural Networks with Non-monotonic Piecewise Linear Activation Functions -- Global Exponential Anti-synchronization of Coupled Memristive Chaotic Neural Networks with Time-varying Delays -- Computer Vision -- Representative Video Action Discovery Using Interactive Non-negative Matrix Factorization -- Image Retrieval Based on Texture Direction Feature and Online Feature Selection -- Interlinked Convolutional Neural Networks for Face Parsing -- Image Tag Completion by Local Learning -- Haarlike Feature Revisited: Fast Human Detection Based on Multiple Channel Maps -- Wood Surface Quality Detection and Classification Using Gray Level and Texture Features -- Aerial Scene Classification with Convolutional Neural Networks -- Signal Processing -- A New Method for Image Quantization Based on Adaptive Region Related Heterogeneous PCNN -- Noisy Image Fusion Based on a Neural Network with Linearly Constrained Least Square Optimization -- A Singing Voice/Music Separation Method Based on Non-negative Tensor Factorization and Repeat Pattern Extraction -- Automatic Extraction of Cervical Vertebrae from Ultrasonography with Fuzzy ART Clustering -- Fast Basis Searching Method of Adaptive Fourier Decomposition Based on Nelder-Mead Algorithm for ECG Signals -- Frequency Recognition Based on Wavelet-Independent Component Analysis for SSVEP-Based BCIs -- Machine Learning -- An MCMC Based EM Algorithm for Mixtures of Gaussian Processes -- Automatic Model Selection of the Mixtures of Gaussian Processes for Regression -- An Effective Model Selection Criterion for Mixtures of Gaussian Processes -- Orthogonal Basis Extreme Learning Algorithm and Function Approximation -- Large Scale Text Clustering Method Study Based on MapReduce -- Representing Data by Sparse Combination of Contextual Data Points for Classification -- A Novel K-Means Evolving Spiking Neural Network Model for Clustering Problems -- Prediction of Individual Fish Trajectory from Its Neighbors' Movement by a Recurrent Neural Network -- Short-term Wind Speed Forecasting Using A Multi-model Ensemble -- Optimization -- Power Control Optimization Method for Transmitted Signals in OFDM Communication Systems -- A Neurodynamic Optimization Approach to Bilevel Linear Programming -- A Nonlinear Neural Network's Stability Analysis and Its kWTA Application -- Continuous-Time Multi-agent Network for Distributed Least Absolute Deviation -- A Fully Complex-Valued Neural Network for Rapid Solution of Complex-Valued Systems of Linear Equations -- Novel Approaches and Applications -- Sparse Representation via Intracellular and Extracellular Mechanisms -- Load Balancing Algorithm Based on Neural Network in Heterogeneous Wireless Networks -- Real-time Multi-Application Network Traffic Identification Based on Machine Learning -- A New Virus-Antivirus Spreading Model -- Exploring Feature Extraction and ELM in Malware Detection for Android Devices -- Data-Driven Optimization of SIRMs Connected Neural-Fuzzy System with Application to Cooling and Heating Loads Prediction.
Keywords: Optical pattern recognition; Data mining; Artificial intelligence; Computer vision; Computer software; Pattern Recognition; Data Mining and Knowledge Discovery; Artificial Intelligence; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity; Mathematical Models of Cognitive Processes and Neural Networks